2016
DOI: 10.22342/jme.7.1.2814.19-30
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Students’ Understanding of Linear Equations With One Variable Using Algebra Tiles

Abstract: This research aimed to describe how algebra tiles can support students' understanding of linear equations with one variable. This article is a part of a larger research on learning design of linear equations with one variable using algebra tiles combined with balancing method. Therefore, it will merely discuss one activity focused on how students use the algebra tiles to find a way to solve linear equations with one variable. Design research was used as an approach in this study. It consists of three phases, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…These findings support the outcomes of previous studies (Agrawal & Morin, ; Saraswati et al, ; Richardson & Bachman, ). These studies have shown that the use of these mathematical manipulatives helps to increase student learning because they encourage relational thinking and promote algebraic reasoning.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings support the outcomes of previous studies (Agrawal & Morin, ; Saraswati et al, ; Richardson & Bachman, ). These studies have shown that the use of these mathematical manipulatives helps to increase student learning because they encourage relational thinking and promote algebraic reasoning.…”
Section: Discussionsupporting
confidence: 92%
“…Algebra tiles provide the students with a means to learn in an experimental way rather than simply studying abstract concepts from a book (Richardson & Bachman, ). It allows the teacher to use concrete models to introduce concepts, instead of focusing on instructional methods that encourage memorization (Caglayan, Olive, & Izsak, ; Saraswati, Ilma, & Putri, ).…”
Section: Related Workmentioning
confidence: 99%
“…It happens because the previous students have also completed the same thing in activity III, namely when finding the number of arithmetic series which guide them well in finding the concept of the number of geometric series. However, there was a group of students who were unable to complete this activity because they did not understand the operations of algebraic forms, especially adding and subtracting similar variables that were difficult to succeed in finding the concept of geometric series (Rachmawati et al, 2019;Saraswati et al, 2016). Therefore, the teacher tried to recall how to combine and replace variables to find a new concept, namely the formula for the number of geometric series.…”
Section: Discussionmentioning
confidence: 99%
“…[26] reviewed the topic of model/curriculum design; while studied topics/issues regarding Mathematical Literacy or PISA / TIMSS reviewed [27], [28], [29], [30] and [31]. The topic of contextual issues / RME was reviewed by [32], [33], [34], [35], and in mathematics education research in the last three years have studied a lot of mathematics learning technology/media including [36], [37], [38], [39], [40]. Judging from the research subjects, mathematics education research now tends to be balanced in choosing research subjects at the primary and secondary education levels.…”
Section: Current Trend Of Mathematics Education Researchmentioning
confidence: 99%